Tax policy in the UK post-Brexit - Freedman, J; Loutzenhiser, G (Oxford University Press, 2022)
Tax matters figured prominently in the Brexit debate. Current signs are, however, that the UK government is not planning the creation of a post-Brexit ‘Singapore on Thames’ as some had predicted. In fact, we are seeing increases to the main corporation tax rate in response to broader international tax developments and the fiscal upheaval caused by the pandemic. Prior to Brexit, the UK already enjoyed considerable freedom in respect of direct taxes including income tax and corporation tax, but less so for VAT; it has more freedom to change the VAT now, if desired, and has already introduced some relatively small amendments to reflect the new state of play. At this point, the government has exercised its new-found freedoms on tax in quite limited ways—most notably in creating freeports which will benefit from special advantageous customs and tax rules, refocusing R&D tax relief towards activity conducted in the UK, making relatively minor changes to tonnage tax, alcohol duties, and air passenger duty, and removing some narrow EU-focused corporation tax measures. However, these new-found tax freedoms come with new-found restrictions, costs, and challenges for both taxpayers and the UK government. There are significant changes on the tax administration front, which generally complicates matters for HMRC as it will have to rely on less extensive and less convenient treaty and OECD avenues of cooperation. On VAT, teething issues as well as longer-term complications have arisen post-Brexit for businesses and consumers. Provisions remain to control the extent of fiscal state aid, albeit in a less restrictive way under the new subsidy control mechanism in the UK/EU Trade and Co-operation Agreement. The strong overall message is that financial and international pressures and constraints are more important to the direction of tax policy than the fact that the UK has left the EU.